2010
DOI: 10.1104/pp.109.152017
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Heterologous Chloroplast Sequence Elements in Transgene Integration and Expression

Abstract: Heterologous regulatory elements and flanking sequences have been used in chloroplast transformation of several crop species, but their roles and mechanisms have not yet been investigated. Nucleotide sequence identity in the photosystem II protein D1 (psbA) upstream region is 59% across all taxa; similar variation was consistent across all genes and taxa examined. Secondary structure and predicted Gibbs free energy values of the psbA 5# untranslated region (UTR) among different families reflected this variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
298
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 207 publications
(301 citation statements)
references
References 72 publications
3
298
0
Order By: Relevance
“…This underscores the importance of the species specificity of chloroplast regulatory sequences. Likewise, details of the homologous recombination process and the deletion of mismatched nucleotides were evident using heterologous flanking sequences (Ruhlman et al, 2010). The translation of native polycistrons without the need for processing to monocistrons has been demonstrated (Barkan, 1988;Zoschke and Barkan, 2015), but the similarity of this process using heterologous polycistrons engineered via the chloroplast genome offered even more direct evidence for this process (De Cosa et al, 2001;Quesada-Vargas et al, 2005).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This underscores the importance of the species specificity of chloroplast regulatory sequences. Likewise, details of the homologous recombination process and the deletion of mismatched nucleotides were evident using heterologous flanking sequences (Ruhlman et al, 2010). The translation of native polycistrons without the need for processing to monocistrons has been demonstrated (Barkan, 1988;Zoschke and Barkan, 2015), but the similarity of this process using heterologous polycistrons engineered via the chloroplast genome offered even more direct evidence for this process (De Cosa et al, 2001;Quesada-Vargas et al, 2005).…”
mentioning
confidence: 99%
“…The expression of precursor proteins via the chloroplast genome demonstrated that cleavage of transit peptides takes place in the stroma and not in the chloroplast envelope (Daniell et al, 1998). Most importantly, the role of nucleus-encoded cytosolic proteins that bind to regulatory sequences and their species specificity were demonstrated using transgenes expressed in chloroplasts (Ruhlman et al, 2010). When the lettuce (Lactuca sativa) psbA regulatory sequence was used to drive transgene expression in tobacco (Nicotiana tabacum) chloroplasts, there was greater than 90% reduction in the accumulation of foreign proteins.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, these UTR sequences, as well as any other sequences with significant homology to the host's plastome, must be used with care, since they can cause unwanted rearrangements (Svab and Maliga, 1993;Staub and Maliga, 1994a;Rogalski et al, 2006Rogalski et al, , 2008McCabe et al, 2008;Zhou et al, 2008;Gray et al, 2009). Reducing the use of DNA fragments with homology to endogenous sequences and/or replacing them with heterologous sequences can decrease the occurrence of unexpected rearrangements (Nadai et al, 2009) but may yield lower transgene expression levels (Ruhlman et al, 2010).…”
mentioning
confidence: 99%
“…Plastid-encoded gene expression has yielded extremely high levels of protein production, with transformants producing 45% (De Cosa et al, 2001) to 70% (Oey et al, 2009) of the transgeneencoded protein per unit of soluble leaf protein and up to 72% (Ruhlman et al, 2010) of the transgeneencoded protein per unit of total leaf protein in tobacco (Nicotiana tabacum). While these expression levels are too high for most metabolic engineering strategies for the production of chemicals, fuels, or materials without creating unwanted stress on the host plant, expression levels can be somewhat controlled by the choice of regulatory elements flanking the transgenes.…”
mentioning
confidence: 99%